STARD1 Functions in Mitochondrial Cholesterol Metabolism and Nascent HDL Formation. Gene Expression and Molecular mRNA Imaging Show Novel Splicing and a 1:1 Mitochondrial Association - Larsen, Michele Campaigne; Lee, Jinwoo; Jorgensen, Joan S.; Jefcoate, Colin R. (Frontiers in Endocrinology, 2020)
STARD1 moves cholesterol (CHOL) from the outer mitochondrial membrane (OMM) to the inner membrane (IMM) in steroidogenic cells. This activity is integrated into CHOL trafficking and synthesis homeostasis, involving uptake through SR-B1 and LDL receptors and distribution through endosomes, ER and lipid droplets. In adrenal cells, one STARD1 is imported into the mitochondrial matrix accompanied by delivery of several hundred CHOL molecules. This transfer limits CYP11A1-mediated generation of pregnenolone. CHOL transfer is coupled to translation of STARD1 mRNA at the OMM. In testis cells, slower CHOL trafficking seems to be limiting. STARD1 also functions in a slower process through ER OMM contacts. The START domain of STARD1 is utilized by a family of genes, which includes additional STARD (forms 3-6) and GRAMD1B proteins that transfer CHOL. STARD forms 2 and 7 deliver phosphatidylcholine. STARD1 and STARD7 target their respective activities to mitochondria, via N-terminal domains (NTD) of over 50 amino acids. The NTD is not essential for steroidogenesis but exerts tissue-selective enhancement (testis>>adrenal). Three conserved sites for cleavage by the mitochondrial processing protease (MPP) generates three forms, each potentially with specific functions, as demonstrated in STARD7. STARD1 is expressed in macrophage and cardiac repair fibroblasts. Additional functions include CHOL metabolism by CYP27A1 that directs activation of LXR and CHOL export processes. STARD1 generates 3.5 kb and 1.6 kb mRNA from alternative polyadenylation. The 3.5 kb form exclusively binds the PKA-induced regulator, TIS11b, which binds to conserved sites in the extended 3’UTR to control mRNA translation and turnover. STARD1 expression also exhibits a novel, slow splicing that slows delivery of mRNA to mitochondria. Stimulation of transcription by PKA is directed by suppression of SIK forms that activate a CRTC/CREB/CBP promoter complex. This process is critical to pulsatile hormonal activation in vivo. sm-FISH RNA imaging shows a flow of single STARD1 mRNA particles from asymmetric accumulations of primary transcripts at gene loci to 1:1 complex of 3.5 kb mRNA with peri-nuclear mitochondria. Adrenal cells are similar but distinguished from testis cells by appreciable basal expression prior to hormonal activation. This difference is conserved in culture and in vivo.